Why Do It Later? Goal Orientation, Self-efficacy, Test Anxiety, on Procrastination - Dorothea Wahyu Ariani; Yuvensius Sri Susilo (LED Edizioni Universitarie, 2018)
Procrastination is a phenomenon that has a double connotes, positive and negative and can occur in all individuals, not least students. Why do individuals procrastinate work completion? There are many factors that cause individuals to procrastinate their works, both external or situational factors and internal or personal factors. The aim of this study was to examine the role of the personal factor in procrastination. Three hundred and sixty-five undergraduate students completed questionnaires that assessed the motivation type of the students' learning, the level of test anxiety, the level to which they procrastinate on doing tasks, and their self-efficacy regarding tasks and tests. The results of this study indicated that procrastination was negatively related to learning-goal orientation and self-efficacy and was positively associated with test anxiety. The results of structural equation modeling testing indicated that self-efficacy mediated the relations between goal orientation and procrastination and between test anxiety and procrastination. These results highlighted the importance of multiple students' type of goal orientation motivation. Self-efficacy and test anxiety consistently affected procrastination with different characteristic. Self-efficacy effected significantly negative on procrastination, while test anxiety effected significantly positive on procrastination. Detailed discussion is presented in this study.